2023
DOI: 10.1186/s12884-023-05420-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pre-eclampsia at St. Mary's hospital lacor, a low-resource setting in northern Uganda, a prospective cohort study

Abstract: Background Pre-eclampsia is the second leading cause of maternal death in Uganda. However, mothers report to the hospitals late due to health care challenges. Therefore, we developed and validated the prediction models for prenatal screening for pre-eclampsia. Methods This was a prospective cohort study at St. Mary's hospital lacor in Gulu city. We included 1,004 pregnant mothers screened at 16–24 weeks (using maternal history, physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The results of this study showed that the WBC count, N count, L count, and PLT count of preeclampsia pregnant women were significantly higher than those of pregnant women at different stages of pregnancy. The main reason for the increase of WBC during pregnancy is the increase of granulocytes caused by bone marrow proliferation and the left shift of the nucleus, that is, more immature WBC appears in the blood circulation ( Awor et al, 2023 ). Although the number of WBCs increased, the chemotaxis and adhesion function of WBCs decreased from the second trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the WBC count, N count, L count, and PLT count of preeclampsia pregnant women were significantly higher than those of pregnant women at different stages of pregnancy. The main reason for the increase of WBC during pregnancy is the increase of granulocytes caused by bone marrow proliferation and the left shift of the nucleus, that is, more immature WBC appears in the blood circulation ( Awor et al, 2023 ). Although the number of WBCs increased, the chemotaxis and adhesion function of WBCs decreased from the second trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Karena kebutuhan medis dan bedah mereka yang unik, pasienpasien ini memerlukan perawatan dari berbagai spesialisasi di pusat perawatan tersier dengan layanan yang lengka. 3 Kembaran parasit adalah anomali yang sangat langka. Insiden pastinya tidak diketahui namun diperkirakan terjadi kurang dari 1 dalam 1 juta kelahiran.…”
Section: Kembarunclassified
“…Globally, preeclampsia complicates approximately 2-8% of the pregnancies [2]. And in Uganda, the incidence of preeclampsia is 4.3% [3]. The presence of convulsions with preeclampsia indicates eclampsia.…”
Section: Introductionmentioning
confidence: 99%